Statistical quality control and operational research: 160 case studies in Indian industries - Prasad, C.R. (Calcutta: Indian Statistical Institute, 1982)
This handbook being published on the occasion of the Golden Jubilee of the Indian statistical Institute is offered in the interest of public service. It gives some illustrative case studies in a variety of industries which are typical of the type of exercises undertaken by the division in the course of their consultancy assignments.
Case studies in statistical quality control -- Engineering -- Electrical and Electronics -- Textiles -- Foundry and steel -- Chemicals, Drugs and Pharmaceuticals -- Process Industries -- Case studies in operational research -- Engineering -- Electrical and Electronics -- Textiles -- Chemicals, Drugs and Pharmaceuticals -- Process Industries
Includes index
Keywords: Statistics; Statistical quality control; Statistical quality control & related topics; Operational research